Gender and food systems research: Key lessons from the Canadian International Food Security Research Fund - Wong, Franz; Danielsen, Katrine; Njuki, Jemimah (CGIAR Collaborative Platform on Gender Research, 2019)
Presented by Franz Wong and Katrine Danielsen (KIT Royal Tropical Institute), and Jemimah Njuki (IDRC) on April 16, 2019, as part of the webinar "Typologies of change – Making sense of gender integration in agriculture and food security research". The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the International Development Research Centre (IDRC).